Student-Teacher Relationships As a Protective Factor for School Adjustment during the Transition from Middle to High School - Longobardi, Claudio; Prino, Laura E.; Marengo, Davide; Settanni, Michele (Frontiers in Psychology, 2016)
A robust body of research has identified school transitions during adolescence, and in particular the transition from middle to high school, as one of the riskiest phases for school failure, being characterized by significant social, emotional and behavioral changes. This transition is critical even with respect to academic achievement: in Italy, the highest frequency of school dropout can be observed in the 9th and 10th grades, partly as a consequence of poor adjustment to the new school context. The impact of students' relationships with their teachers may be particularly relevant during critical developmental periods. Indeed, student-teacher relationships have been widely recognized as protective factors in school adjustment and, in case of negative relationships, also as a factor that increases the risk of maladjustment. Positive and affective student-teacher relationships may play an important role in students' adaptation to the school environment, favoring both academic achievement and adaptive behaviors. The aim of this study was to investigate the effects of the quality of teacher-student relationships, as perceived by pupils, on academic achievement, and problem and prosocial behaviors during the relevant school transition. The sample consisted of 122 students (55% female). We employed a self-report questionnaire to collect information on: demographic characteristics, quality of the relationship with teachers, problem and prosocial behaviors, and academic achievement. Students filled in the questionnaires twice: once during the 8th grade and 1 year later, during their first year of high school (9th grade). Regression analyses indicated that both average and varying levels of closeness with teachers significantly predicted changes in academic achievement: A perceived increase in closeness in 9th grade, as well as a higher mean closeness level, was associated with an increase in academic achievement. In turn, an increase in the level of perceived conflict with teachers significantly predicted an increase in conduct problems and hyperactive behaviors. This study supports the significance of student-teacher relationships as a protective factor during students' transition to high-school. Our findings also highlight the importance of relationship quality in preventing students' risk of school failure.